Preface: Gramsci Dictionary - The World (Il mondo) - Baratta, Giorgio (International Gramsci Journal, 2023)
This is an abstract of the entry on Il mondo (translated literally into English: The World) first published in the Dizionario gramsciano (Gramsci Dictionary, Roma, Carocci, 2009). The world is no longer Eurocentric, and – taking into account the great masses of people in East Asian particular – important consequences are envisaged by Gramsci in the case of a shift in its axis from the Atlantic to the Pacific.